EU crisis policy as judicialization of democracy: Authoritarian European constitutionalism and the negation of popular sovereignty. - Guth, Ralph (Momentum Quarterly, 2013)
In my paper, I want to put the prevailing crisis policy of the EU in a broader context of ‚judicialization‘ of democratic politics. Building on the works on ‚new constitutionalism‘ (mainly by Stephen Gill and Ran Hirschl) and ‚authoritarian statism‘ (Nicos Poulantzas), I thoroughly and critically analyse the ratified EU-regulations and treaties with regard to their impact on democratic freedoms and the competences of legislature bodies. Based on this, I point out that even in the period before the current multiple crises, extensive and intensive judicialization of politics took place; that policies are being enforced increasingly authoritatively and partly outside established European Union law.